Highly efficient photovoltaic energy storage hybrid system based on ultrathin carbon electrodes designed for a portable and flexible power source - Farhadi, Bita; Marriam, Ifra; Yang, Shengyuan; Zhang, Hui; Tebyetekerwa, Mike; Zhu, Meifang; Ramakrishna, Seeram; Rajan, Jose; Zabihi, Fatemeh (Elsevier Ltd, 2019)
Integrated perovskite solar capacitor (IPSC) systems are the new paradigm for power generation and storage. Herein, a novel configuration and combination of materials for an IPSC, theoretically affording a maximized areal capacitance of 2.35 mF cm−2 and exceeding a 25% overall photo-chemical-electricity energy conversion efficiency is reported. A ∼1 μm solid-state photocapacitor is suggested based on a CH3NH3PbI3 photoactive layer, inorganic buffer junctions, an ultrathin nanocarbon border and top electrodes. For the first time, bulk and interfacial imperfections in the perovskite layer are reckoned in simulation, realizing the recombination rate to 14-order of magnitude higher than that in the perfect perovskite structure. The simulation considers the band gap energy, the valance and conduction bands, carrier mobility and carrier density of every individual layer of the designed IPSC. Overall, the results for the areal capacitance, output voltage and photocharging efficiency under various illumination conditions, frequencies and dielectric materials show that the performance of the perovskite power pack is mildly susceptible to external and internal triggers. This ultrathin and sturdy architecture, shows promise for use in self-powered portable and wearable personal devices.